Bankruptcy forecast of ades issuers 2018-2022: comparison of method accuracy and implications of results - Judijanto, Loso (Junal Ilmu Manajemen, 2024)
This research aims to compare the level of precision of four insolvency forecasting models, namely the Grover, Springate, and Zmijewski models to forecast the probability of insolvency of ADES listed companies engaged in the food and beverage sector listed on the IDX. The source used is the company's financial statements during the period 2018-2022. After carrying out calculations with the four models, a comparison is made to see the difference in results between models from year to year. The study results indicate that there is an inequality of results between the Grover model and Altman Z-Score, Springate, and Zmijewski to predict the insolvency of ADES issuers. The Grover model prediction results only produce bankruptcy conditions in 2018, while for 2019 to 2022 it is normal so that it has the highest precision of 80%, followed by the Springate and Zmijewski models with 60% precision, and the Altman Z-Score with 20% precision. In this case, the performance improvements made by the company since 2019 are accommodated by the Grover Model while the other models only accommodate this several years later. The Revised Altman model appears to be the most conservative in providing bankruptcy predictions so that it is more likely to produce bankruptcy predictions even though there have been improvements in company performance for several years. The results of the analysis provide lessons regarding the validity of the model and the level of conservativeness of the model in accommodating performance improvements made by different issuers.